2012
DOI: 10.1002/hec.2880
|View full text |Cite
|
Sign up to set email alerts
|

“Do I Stay or Do I Go?”—job Change and Labor Market Exit Intentions of Employees Providing Informal Care to Older Adults

Abstract: We studied the effects of providing informal eldercare on the turnover intention of men and women in a group of workers who were also the main carers providing support to a dependent older person with substantial care needs. The intention of male and female workers to change jobs and exit the labor market is shaped by the different characteristics of informal caregiving. Time-based conflicts between informal care and paid work are associated with a higher relative risk of anticipating job changes for female wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 53 publications
2
49
0
1
Order By: Relevance
“…Informal caregiving, however, involves both physically and mentally straining elements and is thus different from providing economic support. Looking specifically at informal caregiving, a study from Austria has shown that a time-based conflict between informal eldercare and paid work was related to the intended job change of female workers and that the intensity of caregiving provided was related to male workers' anticipated labor market exit (25). However, to our knowledge no studies have investigated the association between informal caregiving and sickness absence due to paid work.…”
mentioning
confidence: 97%
“…Informal caregiving, however, involves both physically and mentally straining elements and is thus different from providing economic support. Looking specifically at informal caregiving, a study from Austria has shown that a time-based conflict between informal eldercare and paid work was related to the intended job change of female workers and that the intensity of caregiving provided was related to male workers' anticipated labor market exit (25). However, to our knowledge no studies have investigated the association between informal caregiving and sickness absence due to paid work.…”
mentioning
confidence: 97%
“…Since the majority of employed males tend to possess relatively less flexible work arrangements, they may be more inclined to leave the workforce altogether when caregiving demands increase. An investigation of informal elder care by employed individuals in Austria (Schneider et al, 2012) finds that flexible work arrangements facilitate the attachment of female workers to their jobs and the labour market. The intensity of personal care provided to an older relative is significantly positively related to male workers' relative risk of labour market exit.…”
Section: Discussionmentioning
confidence: 99%
“…There was not the corresponding impact in caregiving hours and lower wages among male informal caregivers. Schneider et al [34] found time-based conflicts between informal eldercare and paid work. It was positively related to job changes of female workers but not of their male counterparts.…”
Section: Discussionmentioning
confidence: 99%